Violation of the Principles of Politeness Teachers and Students in Learning Interaction - Imroh, Lilik Al; Zulaeha, Ida; Pristiwati, Rahayu (Universitas Negeri Semarang, 2022)
This research was motivated by the discovery of violations of the principles of politeness in the speech of teachers and students in learning interactions. This study aims to describe the form of speech politeness violations of teachers and students in learning interactions in madrasas. The data collection method used is the listening method with recording and note-taking techniques using data cards. The method used in data analysis is a normative method, matching data based on the criteria of politeness principles. Data analysis used Leech's theory of politeness principles. The results of the research on violations of politeness principles in learning interactions in madrasas are it is found that the utterances of teachers and students violate the principles of politeness, namely: 10 utterances that violate the maxims of wisdom; 6 utterances violate the maxim of generosity; 8 utterances violate the maxim of appreciation; 7 utterances violate the maxim of simplicity; 7 utterances violate the maxim of agreement; and 6 utterances violate the maxim of sympathy. Violations occur when teachers and students interact during the learning process both inside and outside the classroom.